2022
DOI: 10.1007/s10964-022-01613-5
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Stop Bullying following a Condemning, Empathy-Raising, or Combined Message from a Teacher – Do Students’ Empathy and Callous-Unemotional Traits Matter?

Abstract: Knowing which intervention strategies work best and for which student is essential for teachers when they intervene in cases of bullying. The effects of teachers’ (1) condemning, (2) empathy-raising, and (3) combined (including elements of both) messages on students’ intention to stop bullying were tested in a between-subject experimental design. A total of 277 seventh grade students (Mage = 12.93, SD = 0.49; 47% female) were asked to imagine they had bullied a peer and were invited to a discussion with a teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This could explain the lower compliance of male bullying perpetrators with teachers' requests to stop bullying. This is in line with the results of Johander et al (2022), who also found that boys were less likely to say that they would stop their bullying behavior as a response to an intervention. This lower responsiveness of male perpetrators to the interventions could also be the reason why victimization was more likely to continue for male victims.…”
Section: Discussionsupporting
confidence: 89%
“…This could explain the lower compliance of male bullying perpetrators with teachers' requests to stop bullying. This is in line with the results of Johander et al (2022), who also found that boys were less likely to say that they would stop their bullying behavior as a response to an intervention. This lower responsiveness of male perpetrators to the interventions could also be the reason why victimization was more likely to continue for male victims.…”
Section: Discussionsupporting
confidence: 89%
“…Whether or not youth admit to bullying also has important ramifications for intervention. For example, targeted interventions have made distinctions between confronting and non-confronting approaches when intervening with a perpetrator (e.g., Johander et al, 2022 ), but an important first step is whether a perpetrator even acknowledges their bullying behavior. In addition, lower-status victims self-reported more concurrent bullying than high-status non-victims, despite not being seen as a bully by their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of CU on individuals get attention in recent years, the majority of the existing research focus on the relationship between CU and violent behaviours in real life such as bullying and behavioural disorders. [4] However, the relationship between CU and different types of Internet use is still unclear, and there are few studies on adolescent objectives, and most of them are reform school students instead of ordinary middle school students. Therefore, studies on relation of CU and Internet use remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%